Forecasting Financial Inclusion and Its Impacts on Poverty and Inequality: A Comparative Study in ASEAN - Wahyudi, Setyo Tri; Nabella, Rihana Sofie; Badriyah, Nurul; Sari, Kartika; Radeetha, Radeetha (Jurnal Ekonomi Kuantitatif Terapan; Vol 17 No 1 (2024): Vol. 17, No. 1, Februari 2024 (pp.1-154)DO - 10.24843/JEKT.2024.v17.i01.p08, 2024)
Financial inclusion has played a vital role in eradicating poverty and inequality in some developing countries over the last few decades. In ASEAN, the growth of financial inclusion is so rapid that it reaches every element of society. Therefore, the purpose of this study is to examine forecasts of financial inclusion, poverty, and inequality in ASEAN. In addition, the study also analyzes the correlation between financial inclusion, poverty, and inequality in ASEAN. The study uses the ARIMA and GMM models for the study period from 2000 to 2022. Projections show that most ASEAN countries have experienced an increase in the long-term financial inclusion index, with Thailand leading the ranking, followed by Malaysia. However, the role of financial inclusion in poverty does not seem to be so significant in the short term, most likely due to the still-difficult access for low-income groups.